A comparative evaluation of intravenous dexmedetomidine and oral clonidine in attenuating the rise in intra ocular pressure - K., Yadhuraj M.; P., Somasekharam; M., Vinay D.; U. K., Akhil Rao (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Administration of Suxamethonium, laryngoscopy and intubation is associated with rise in intraocular pressure (IOP). The need to attenuate rise in IOP is of utmost importance, especially in patients with perforating injury of the eyeball. The present study was undertaken to compare the effectiveness of intravenous Dexmedetomidine 0.4μg/kg and oral Clonidine 3μg/kg in attenuating the rise in IOP following administration of suxamethonium, laryngoscopy and intubation. Methods: 150 patients of ASA I or II, aged between 18-60 years, who were posted for elective non-ophthalmic surgery requiring general anaesthesia were included in this study. Patients were randomly divided into 3 groups with 50 patients in each group. Group-D: Received 0.4μg/kg IV dexmed in 10ml sterile water, over 10 min before induction. Group-C: Received 3μg/kg oral clonidine two hours prior to surgery. Group-S: Control group. Results: IOP, MAP, and HR were recorded at baseline, before induction, after induction, 1 min, 3 min and 5 min after administration of suxamethonium. Although Suxamethonium laryngoscopy and intubation increased IOP in all the 3 groups there was significant reduced rise in IOP noted in dexmed group and clonidine group compared to study group (p= <0.001). Furthermore, patients in dexmed group had lesser rise in IOP compared to clonidine group (p= <0.001). Conclusions: We concluded that both intravenous dexmedetomidine 0.4μg/kg and oral clonidine 3μg/kg, significantly attenuated the rise in IOP associated with administration of suxamethonium, laryngoscopy and intubation. However intravenous dexmedetomidine proved better than oral clonidine in attenuating the rise in IOP.